Fabrication Methods and Performance in Fuel Cell and Steam Electrolysis Operation Modes of Small Tubular Solid Oxide Fuel Cells: A Review - Orera, Victor M.; Laguna-Bercero, Miguel A.; Larrea, Angel (Frontiers in Energy Research, 2014)
Higher energetic density, better resistance to thermal stresses and smaller starting times as compared with conventional planar stacks, make the so-called microtubular SOFC (mT-SOFCs with diameters in the millimeter size region) devices suitable for portable applications in the sub kW energy range. However, fabrication of mT-SOFCs is a challenging process where a number of ceramic layers with different compositions and characteristics have to be placed together in the cylindrical device. Several co-sintering processes have to be performed at different temperatures and using distinct atmospheres to complete cell fabrication. In this review we summarize recent activity in the field of fabrication and characterization of mT-SOFCs, including the use of mT-SOFCs for steam electrolysis.